Older adults' integration in the labour market: a global view. Issue 4 (9th April 2021) - Börsch-Supan, Axel; Hanemann, Felizia; Beach, Brian; Halimi, Didier; Harding, Susana; van der Waal, Marieke; Watanabe, Daisuke; Staudinger, Ursula M.
Abstract: What governs labour force participation in later life and why is it so different across countries? Health and labour force participation in older ages are not strongly linked, but we observe a large variation across countries in old-age labour force participation. This points to the important role of country-specific regulations governing pension receipt and old-age labour force participation. In addition to the statutory eligibility age for a pension, such country-specific regulations include: earnings tests that limit the amount of earnings when pension benefits are received; the amount of benefit deductions for early retirement; the availability of part-time pensions before normal retirement; special regulations that permit early retirement for certain population groups; and either subsidies or extra costs for employers if they keep older employees in their labour force. This paper asks two questions: Can we link a relatively low labour force participation at ages 60–64 to country-specific regulations that make early retirement attractive? and Can we link a relatively high labour force participation at ages 65–74 to country-specific regulations that make late retirement attractive? To answer these questions, we compared the experiences in a set of developed countries around the world in order to understand better the impact of country-specific rules and laws on work and retirement behaviour at older ages and, by consequence, on the financial sustainability of pension systems.